How do we learn professional ethics? Professional competences, embodiment and ethics in physiotherapy education in Norway - Dahl-Michelsen, Tone; Groven, Karen Synne (Critical Studies in Teaching and Learning, 2023)
This paper aims to enhance the understanding of how physiotherapy students develop professional ethical insight. The empirical data is based on participant observations and in-depth interviews with first-year students attending skills training classes in one of Norway’s four physiotherapy bachelor programmes. Theoretically, this paper is framed within Merleau-Ponty’s and Daly’s embodied approaches to ethics. The analysis pays special attention to the concepts of ethical insight, ethical sensibility and hyper-reflection. The findings are presented according to two themes: ‘embodying tacit care’ and ‘in-between abstract and embodied ethics’. In the discussion, we address students’ development of ethical sensibility and lack of hyper-reflection skills. Ultimately, we argue that while physiotherapy education should embrace the unique nature of skills training as an opportunity to stimulate students to develop their ethical sensibility, at the same time, the curriculum must also emphasise hyper-reflection (critical thinking). We also discuss how educators can organise their curriculum and teaching in a way that enhances the potential for students to develop professional ethical insight